Analisis Komparatif Perspektif KHI dan Fiqih Imam Syafi’i tentang Hukum Ihdad bagi Perempuan - Zamroni, Muhammad; Ulum, Hairul (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
The article discusses the comparison of Ihdad provision between KHI and Imam Syafi’i. KHI states that Ihdadmust be done during ‘iddah for wives left by theirhusband due to death as a symbol of grief and avoidingslender. These wives, according to Imam Syafi’i, must doIhdad in case they are adults, children, kafir dzimmis, orslaves. The distinctive is also found in the lawconsequence that should be accepted during Ihdad. InKHI there is no law that sets things forbidden duringIhdah in details as Imam Syafi’i’s fiqh provision. Keywords : KHI, Fiqh, Ihdad Law.